Natural Receptor- and Ligand-Based Chimeric Antigen Receptors: Strategies Using Natural Ligands and Receptors for Targeted Cell Killing - Gianna M. Branella; Harold Trent Spencer (Cells, 2021)
Chimeric antigen receptor (CAR) T-cell therapy has been widely successful in the treatment of B-cell malignancies, including B-cell lymphoma, mantle cell lymphoma, and multiple myeloma; and three generations of CAR designs have led to effective FDA approved therapeutics. Traditionally, CAR antigen specificity is derived from a monoclonal antibody where the variable heavy (VH) and variable light (VL) chains are connected by a peptide linker to form a single-chain variable fragment (scFv). While this provides a level of antigen specificity parallel to that of an antibody and has shown great success in the clinic, this design is not universally successful. For instance, issues of stability, immunogenicity, and antigen escape hinder the translational application of some CARs. As an alternative, natural receptor- or ligand-based designs may prove advantageous in some circumstances compared to scFv-based designs. Herein, the advantages and disadvantages of scFv-based and natural receptor- or ligand-based CAR designs are discussed. In addition, several translational aspects of natural receptor- and ligand-based CAR approaches that are being investigated in preclinical and clinical studies will be examined.